2020
DOI: 10.3389/fpsyg.2020.00355
|View full text |Cite
|
Sign up to set email alerts
|

Friends, Lovers or Nothing: Men and Women Differ in Their Perceptions of Sex Robots and Platonic Love Robots

Abstract: Physical and emotional intimacy between humans and robots may become commonplace over the next decades, as technology improves at a rapid rate. This development provides new questions pertaining to how people perceive robots designed for different kinds of intimacy, both as companions and potentially as competitors. We performed a randomized experiment where participants read of either a robot that could only perform sexual acts, or only engage in non-sexual platonic love relationships. The results of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
2
26
1
Order By: Relevance
“…Research on sex doll owners has revealed a diversity of use patterns that include sexual interaction (e.g., sexual intercourse with the doll) but also social interaction (e.g., dining and watching TV with the doll) as well as physical care work (e.g., washing, powdering, and dressing the doll). Another research strand explores attitudes toward sex robots, intentions to use and to buy a sex robot with the help of surveys and vignette experiments where the robot is described to the participants or pictures of the robot are shown ( Szczuka and Krämer, 2017a , b ; Appel et al, 2019 ; Nordmo et al, 2020 ; Oleksy and Wnuk, 2021 ). Even though first theoretical models of the psychological mechanisms of sex robot use have been presented ( Szczuka et al, 2019 ), so far, no empirical data are available on sexual and social interactions with actual sex robots or about long-term sex robot users.…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…Research on sex doll owners has revealed a diversity of use patterns that include sexual interaction (e.g., sexual intercourse with the doll) but also social interaction (e.g., dining and watching TV with the doll) as well as physical care work (e.g., washing, powdering, and dressing the doll). Another research strand explores attitudes toward sex robots, intentions to use and to buy a sex robot with the help of surveys and vignette experiments where the robot is described to the participants or pictures of the robot are shown ( Szczuka and Krämer, 2017a , b ; Appel et al, 2019 ; Nordmo et al, 2020 ; Oleksy and Wnuk, 2021 ). Even though first theoretical models of the psychological mechanisms of sex robot use have been presented ( Szczuka et al, 2019 ), so far, no empirical data are available on sexual and social interactions with actual sex robots or about long-term sex robot users.…”
Section: Sexual Interaction With Digital Technologiesmentioning
confidence: 99%
“…At the microsystem level, we can expect that interacting with Nimani could lead to new technology-oriented conditioned partner preferences (as previously described), but also to the co-construction of new proximal dynamics with individuals, groups, and institutions. For instance, as part of our techno-subsystem [ 153 ], erobots can generate new experiences with families, friends, and partners, such as: considering using erobots [ 219 , 265 ], forming strong bonds with artificial agents [ 50 , 260 , 261 ], changing marriage institutions, and engaging in consensual non-monogamy with machines [ 4 ]. They could also lead to the advent of new health, legal, educational, and entertainment services dedicated to human–machine erotic interaction (e.g., applications, stores, organisations).…”
Section: Human-erobot Interaction and Co-evolution Modelmentioning
confidence: 99%
“…The HEICEM’s structure highlights multiple levels of investigation and analysis, which require different disciplines—from humanities and Sexology, to neurosciences, AI and HMI, and cognitive, social, and cultural sciences—to weigh in, if we want to fully grasp the factors and variations of our co-evolution with erobots. Noteworthy, at the moment, some of these phenomena are difficult to examine empirically without solely relying on self-report and hypothetical scenarios [ 87 , 219 , 265 ], partly due to the unavailability, high price, and/or novelty of (sophisticated) erobotic systems. Others, however, can already be observed (and studied)—to various degrees—through individuals, communities, and cultures related to: digi/techno sexuality [ 21 , 200 , 283 ], cybersex (or online sexuality; [ 67 , 85 ]), hentai (i.e., manga or anime pornography; [ 301 ]) and otakuism (i.e., interests in animation, manga, and games, often incorporating (non-)fictional technology; [ 11 , 304 ]), dolls [ 87 , 104 , 166 , 174 , 280 , 294 ], toys [ 86 , 89 , 90 , 138 , 247 , 253 ], platforms [ 49 ], games [ 80 ], teledildonics [ 85 , 107 , 200 ], (VR/AR/MR) pornography [ 254 , 275 ], (AI-powered) dating applications [ 197 , 208 , 281 ], artificial partners [ 87 , 112 , 160 , 200 , 219 , 237 , 307 ], as well as objectophilia, agalmatophilia/pygmalionism, and mechanophilia (i.e., respectively, the (sexual and/or romantic) attraction to objects, statue/dolls/mannequins, and machines; [ 102 , 317 ].…”
Section: Human-erobot Interaction and Co-evolution Modelmentioning
confidence: 99%
“…Some authors [45] focused on relationships, concretely on jealousy. As we saw in the interactions between humans and robots, as the manufacture of sexbots is perfected, the relationships between humans and these robots will become more complex.…”
Section: (A) Gender Approachesmentioning
confidence: 99%